Analisis Pengaruh Nilai Tukar Rupiah, Inflasi, Tingkat SBI, Dan Return On Asset (ROA) Terhadap Harga Saham Sektor Perbankan - Lis Lestari Sukartiningsih; Saritta Witgryta Putri (Akubis : Jurnal Akuntansi dan Bisnis, 2022)
This study aims to analyze the effect of the rupiah exchange rate, inflation, SBI rate, and Return On Assets (ROA) on stock prices of banking sector companies for the 2014-2018 period. The data used in this study is secondary data obtained from published data from Bank Indonesia and the Central Bureau of Statistics which include the rupiah exchange rate, inflation, and SBI rates. Meanwhile, the closing share prices of banking sector companies were obtained from the Indonesia Stock Exchange. The population used is 41 banking sector companies listed on the Indonesia Stock Exchange. The sample selection criteria used a purposive sampling method and obtained a sample of 12 companies. The type of research used in this research is explanatory research which explains the influence of the rupiah exchange rate, inflation and SBI rates on stock prices. The results of the analysis of the rupiah exchange rate, inflation and the SBI rate have no simultaneous effect on the dependent variable on stock prices. Partially the rupiah exchange rate variable has no effect on banking sector stock prices and inflation has no effect on banking sector stock prices. Meanwhile, the SBI level partially affects the share price of the banking sector. The variable that has the most dominant effect is the SBI level variable.